IMPROVING CONFIDENCE ENGINEERING GROUP COUNSELING SERVICES THROUGH PLAY IN HIGH SCHOOL STATE 1 ANGKOLA TIMUR ACADEMIC YEAR 2015-2016 - Rosnasari Marbun (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The study was based on issues found in research that is the irrational fear when dealing with people, it arises because of the lack of confidence of students. Problems can be formulated as follows: (1) How confident students before and after the service group in the experimental group? (2) How confident students before and after the service in the control group? (3) How is the effectiveness of group counseling services to the increasing confidence of students? The purpose of this study was to determine the effectiveness of group counseling services to the increasing confidence of students. Places studies in SMA 1 Angkola Timur. A population of 294, the samples taken in the experimental group that is class XI-3 10 and a control group of class XI IPS-4 amounted to 10 the total number of samples 20. Researchers providing counseling services group four times. The method used was Quasi Experimental Desaign with nonequivalent control group design shape desaign. Data collection techniques using a Likert scale questionnaire. Data were analyzed using Excel and SPSS program version 20 by using the Wilcoxon signed rank test and one sample kolmogrov Smirnov test. Researcher research results obtained in the experimental group was 81.03 84.11 in the control group. Test the hypothesis produce the experimental class Z on pretest-posttest with a value of -2.087 and signed pretest-posttest valued 0.05. While in the control class Z on pretest-posttest with a value of -2.805 and signed pretest-posttest worth 0.05. At posttest posttest control experiment and signed (2-tailed) 983 experimental group and the control group 999.In conclusion increased significantly between pretest and posttest experiment as well as the pretest and posttest control. But research experimental group was higher than the control group. Suggestions researcher for the school is that certainly encourages group counseling to all students.Keywords: Confidence, Guidance group